(3cJGH aj GdGOHs - (3GdMSf Hf bGSe Hf YHO Gddg GdeQGOj GdeUQj, HOQ GdOjf CHh eMeO, GHf Ge bGSe , J (B749 (3g` s
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI GdMeO ddg GdPj CYdG ebGe Cgd GdGOH GdaUd GdChd aj GdSeGA hGdfLhe s
(3BNQgG (B:s
(3ef BNQ GdehLhO aHcj Gdbhe dHcGFI hGefhG Ydi UGdM OYGFI adeG aQZ Cbjd GdfGS Edjg hCcKQ hGf JbQjXg hGdKfGA Ydjg s
(3Vef eLehY , JQJjHgG (B: 2s
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B2 - (3U (B211 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B3 - (3U (B271s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3MGdI GdfSNI LjOI s
Keywords: (3eJaQbGJs